Law and equity in Hobbes. Issue 1 (2nd January 2016) - Sorell, Tom
Abstract : Equity is clearly central to Hobbes's theory of the laws of nature, and it has an important place in his doctrine of the duties and exercise of sovereignty. It is also prominent in his general theory of law, especially as it is articulated in the late Dialogue between a Philosopher and a Student of the Common Laws of England. Still, it is not more central to Hobbes's ethics, politics and legal philosophy than his concept of justice, or even as central. On the contrary, his theory of justice is presupposed by his views about equity – in the sense that fidelity to a social contract is a condition of adjudication and definitive interpretation of law. Nor does equity contribute to a genuinely anti-authoritarian strand in Hobbes's political philosophy. It is not as if, between the lines of that philosophy, Hobbes is a liberal. He does not think that the sovereign should exercise self-restraint because liberty and autonomy are good and sovereign self-restraint creates a space for both. Rather, he thinks that heavy-handed rule saps initiative, wealth and other resources from the people, making them less able to participate in or finance military action or internal state security. In other words, heavy-handed rule can make it harder for the sovereign to discharge the principal duty of sovereignty – ensuring public safety.